Advances in per- and polyfluoroalkyl substances (PFAS) detection and removal techniques from drinking water, their limitations, and future outlooks - Zahra Zahra; Minkyung Song; Zunaira Habib; Sadaf Ikram (Emerging Contaminants)
The widespread presence of per- and polyfluoroalkyl substances (PFAS) in the environment poses a serious threat due to their persistent nature and harmful effects on human health and ecosystems. In this context, there is an imperative need for developing and improving methods to identify and eliminate these contaminants. Different detection techniques that are being used for PFAS detection are discussed. The details of detection mechanism of these techniques, their limitations and future areas of research for their optimization and improvement in detection efficiencies are also discussed in this review. Besides, this article provides a baseline for anticipating the advanced treatment technologies for PFAS in drinking water. We focus on the effectiveness of different removal techniques (physical, biological and chemical advancements) for eliminating various types of short and long chain PFAS. More so, the methods for the removal of PFAS are also explained with their limitations and future outlooks. Their pros and cons and limitations that need to be overcome and could be the potential future research. We included the recent literature and encompassed the information of PFAS related to guidelines, analytical techniques to determine PFAS and treatment or removal technologies. Conclusively, this study suggests that a combination of treatment methods will likely be necessary for effective PFAS remediation in water.